CURRENT PROBLEMS OF MODERN ECOLOGY IN UZBEKISTAN AND MEASURES TO STABILIZE EMISSIONS INTO THE ENVIRONMENT - Mehrangiz Shomuratova (Web of Journals Publishing, 2024)
This article examines environmental problems in different regions of Uzbekistan and their solutions
Keywords: Ecology, Uzbekistan, population, environment, pollution, radiation, drinking water.